GGE Biplot Analysis for Yield Stability of Lentil Genotypes (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at three different locations of Bangladesh Agricultural Research Institute viz., at PRC, Ishurdi, Pabna, at PRSS, Joydebpur, Gazipur and RARS, Jashore, during the period November to March in 2014-15 and 2015-16. The experiment was laid out in Randomized Complete Block Design with three replications. Variance analysis showed significant interaction between genotype and environment on yield and its related traits. The highest yield was recorded in genotypes BARI Masur-7 followed by BARI Masur-6, BARI Masur-5, BARI Masur-4 and the lowest was in BLX-66004-12. The PCA (Principal component analysis) scores of a genotype in the GGE analysis indication of the stability or adaptation over environments. GGE biplot analysis related that the PC1 and PC2 for different traits, i.e. 80.8% and 11.7% for days to flowering, 72.4% and 18.7% for days to maturity, 66.3% and 15.4% for plant height, 73.8% and 17.3% for pods/plant, 70.1% and 22.8% for 100 seed weight and 38.37% and 31.04% for yield of the total variation, respectively. Considering regression co-efficient values and also biplot analysis most stable variety was BARI Masur-4 followed by BARI Masur-5 and BARI Masur-6 and lowest stable variety was BLX-05002-6. Among the six environments, Ishurdi 2014-15 and Gazipur 2014-15 were most discriminating (informative) and Jashore 2014-15 and Jashore 2015-16 were less discriminating. Among two years (2014-15 and 2015-16) at different location 2015-16 was found favorable for lentil production.Bangladesh J. Agril. Res. 46(3): 307-320, September 2021